DETERMINANTS OF CUSTOMER RE-INTEREST IN USING THE MOBILE BANKING OF BANK SYARIAH INDONESIA: A REVIEW OF THE TECHNOLOGY ACCEPTANCE MODEL THEORY - Marfuah, Marfuah; Ratnaningrum, Devi (Media Riset Akuntansi, Auditing & Informasi, 2024)
The purpose of this research is to determine the influence of perceived usefulness, compatibility, advantages, risk, trust, perceived ease of use, and security on customer interest in using Bank Syariah Indonesia mobile banking in Yogyakarta. The population of this research is customers who use Bank Syariah Indonesia mobile banking in the Special Region of Yogyakarta. Using the convenience sampling method, 170 Bank Syariah Indonesia customers were selected as the research sample. The research results concluded that the variables of perceived benefit, perceived ease of use, trust and security were proven to have a significant positive effect on customers' re-interest in using Bank Syariah Indonesia mobile banking. Meanwhile, the compatibility, advantages and risk variables were not proven to have a significant positive effect on customer interest in using Bank Syariah Indonesia mobile banking. The results of this research contribute to banking institutions to always improve the security and ease of use of the mobile banking system, so that customers increasingly feel the benefits and trust in it so that customers will increase their interest in using mobile banking.